![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
d,155-10(x+1)=55
10(x+1) = 155 - 55
10(x+1) = 100
x+1 = 100 : 10
x+1 = 10
x = 10 - 1 =9
e,6(x+\(2^3\))+40=100
6(x+\(2^3\)) = 100 - 40
6(x+\(2^3\)) = 60
(x+\(2^3\)) = 60 : 6
(x+\(2^3\)) = 10
x = 10 - \(2^3\)
x = 10 - 8 = 2
f,\(2^2\)(x+\(3^2\))-5=55
\(2^2\)(x+\(3^2\)) = 55 + 5
\(2^2\)(x+\(3^2\)) = 60
(x+\(3^2\)) = 60 : \(2^2\)
(x+\(3^2\)) = 60 : 4
(x+\(3^2\)) = 15
x + 9 = 15
x = 15-9=6.
Hok tốt !
d) \(155-10\left(x+1\right)=55\)
\(\Rightarrow10\left(x+1\right)=155-55\)
\(\Rightarrow10\left(x+1\right)=100\)
\(\Rightarrow x+1=100:10\)
\(\Rightarrow x+1=10\)
\(\Rightarrow x=10-1\)
\(\Rightarrow x=9\)
Vậy x = 9
e) \(6\left(x+2^3\right)+40=100\)
\(\Rightarrow6\left(x+2^3\right)=100-40\)
\(\Rightarrow6\left(x+2^3\right)=60\)
\(\Rightarrow x+2^3=60:6\)
\(\Rightarrow x+2^3=10\)
\(\Rightarrow x+8=10\)
\(\Rightarrow x=10-8\)
\(\Rightarrow x=2\)
Vậy x = 2
f) \(2^2\left(x+3^2\right)-5=55\)
\(\Rightarrow2^2\left(x+3^2\right)=55+5\)
\(\Rightarrow2^2\left(x+3^2\right)=60\)
\(\Rightarrow4\left(x+9\right)=60\)
\(\Rightarrow x+9=60:4\)
\(\Rightarrow x+9=15\)
\(\Rightarrow x=15-9\)
\(\Rightarrow x=6\)
Vậy x = 6
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có
<=> x - 10 +40 = - 22 - x - 6
<=> x + 30 +2 8 + x =0
<=> 3x=58
=>x=58/3
x-10+40=-22-x-6
\(\Rightarrow\)x+30=-28-x
\(\Rightarrow\)2x=-58
\(\Rightarrow\)x=-29
Vậy x=-29
![](https://rs.olm.vn/images/avt/0.png?1311)
1a) \(\frac{x-3}{x+7}=\frac{-5}{-6}\)
=> \(\frac{x-3}{x+7}=\frac{5}{6}\)
=> (x - 3).6 = 5.(x + 7)
=> 6x - 18 = 5x + 35
=> 6x - 5x = 35 + 18
=> x = 53
b) \(\frac{x-7}{x+3}=\frac{4}{3}\)
=> (x - 7). 3 = (x + 3). 4
=> 3x - 21 = 4x + 12
=> 3x - 4x = 12 + 21
=> -x = 33
=> x = -33
c) \(\frac{x-10}{6}=-\frac{5}{18}\)
=> (x - 10) . 18 = -5 . 6
=> 18x - 180 = -30
=> 18x = -30 + 180
=> 18x = 150
=> x = 150 : 18 = 25/3
d) \(\frac{x-2}{4}=\frac{25}{x-2}\)
=> (x - 2)(x - 2) = 25 . 4
=> (x - 2)2 = 100
=> (x - 2)2 = 102
=> \(\orbr{\begin{cases}x-2=10\\x-2=-10\end{cases}}\)
=> \(\orbr{\begin{cases}x=12\\x=-8\end{cases}}\)
e) \(\frac{7}{x}=\frac{x}{28}\)
=> 7 . 28 = x . x
=> 196 = x2
=> x2 = 142
=> \(\orbr{\begin{cases}x=14\\x=-14\end{cases}}\)
f) \(\frac{40+x}{77-x}=\frac{6}{7}\)
=> (40 + x) . 7 = (77 - x).6
=> 280 + 7x = 462 - 6x
=> 280 - 462 = -6x + 7x
=> -182 = x
=> x = -182
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a. $\frac{7}{x}=\frac{x}{28}$
$\Rightarrow x^2=7.28=196=14^2=(-14)^2$
$\Rightarrow x=\pm 14$
b.
$\frac{x+10}{x+17}=\frac{3}{4}$
$\Rightarrow 4(x+10)=3(x+17)$
$\Rightarrow 4x+40=3x+51$
$\Rightarrow x=11$
c.
$\frac{40+x}{77-x}=\frac{6}{7}$
$\Rightarrow 7(40+x)=6(77-x)$
$\Rightarrow 280+7x=462-6x$
$\Rightarrow 13x=182$
$\Rightarrow x=182:13=14$
Lời giải:
a. $\frac{7}{x}=\frac{x}{28}$
$\Rightarrow x^2=7.28=196=14^2=(-14)^2$
$\Rightarrow x=\pm 14$
b.
$\frac{x+10}{x+17}=\frac{3}{4}$
$\Rightarrow 4(x+10)=3(x+17)$
$\Rightarrow 4x+40=3x+51$
$\Rightarrow x=11$
c.
$\frac{40+x}{77-x}=\frac{6}{7}$
$\Rightarrow 7(40+x)=6(77-x)$
$\Rightarrow 280+7x=462-6x$
$\Rightarrow 13x=182$
$\Rightarrow x=182:13=14$
![](https://rs.olm.vn/images/avt/0.png?1311)
40 - 2.(x - 6) = 10
2.(X - 6) = 40 - 10
2.(x - 6) = 30
x - 6 = 30 : 2
x - 6 = 15
x = 15 + 6
x = 21
40 - 2 ( x - 6 ) = 10
2 ( x - 6 ) = 40 - 10
2 ( x - 6 ) = 30
x - 6 = 30 : 2
x - 6 = 15
x = 15 + 6
x = 21
Vậy x = 21